OXIDATION STATE OF IRON IN SILICATE GLASSES AND MELTS: A THERMOCHEMICAL MODEL - Ottonello G.; Moretti R.; Marini L.; Vetuschi Zuccolini M. (My University, 2001)
The acid and base dissociation constants of FeO and Fe2O3 components in silicate melts are defined in terms of observed relationships between atomistic properties of dissolved oxides (nephelauxetic parameters, electronegativity, fractional ionic character of the bond) and polymerization constants in simple systems. These constants are obtained from the Toop-Samis model depicting the Gibbs free energy of mixing of binary MO-SiO2 melts, which is coupled with the amphoteric treatment of altervalent dissolved oxides. Model parameterization is carried out on the basis of the extended set of data concerning thermodynamic activity of FeO in melts buffered by equilibrium with pure iron metal and a gaseous phase and on the various measurements of bulk redox state of iron in chemically complex melts at various T, fO2 conditions. Dissociation constants are related to thermodynamic parameters of the main dissolved species (O2-, Fe2+, Fe3+, FeO2-) without any significant error progression. As an ancillary result, thermochemical calculations allow to quantify to some extent the systematic errors in the FeII/FeIII bulk redox ratio arising from the utilization of Mossbauer spectroscopy on quenched melts and glasses.
Keywords: MELTS; GLASSES; IRON REDOX; POLYMER MODEL; MOSSBAUER